Método de seleção de faixa para estudo de traçado para obras lineares de infraestrutura de transportes - Freire, Pedro Almi da Costa (2014)
The study of horizontal alignment for linear works presented is an issue of paramount importance in the design and definition of the guidelines to be studied for the preparation of transport infrastructure projects. Setting the tracing of a track must be made observing the result of the study of alignment alternatives and comparing them, mathematically there is infinite possibilities for alignment alternatives between successive points making it difficult to choose a single solution. The difficulty in defining criteria and objective parameters for determining an area of study and therefore the best alternative route led the study presented. The current trace analysis is limited to pre-set guidelines on a limited number, which can induce choices paths leading unwanted higher costs and operating and maintenance conditions for future route. It is proposed a better range setting method for the study of horizontal alignment for transport infrastructure projects based on topographic data considering deploying and operating costs. The suggested method is the three-dimensional scan of the region which includes the work under study, pointing out the best tracks for development based on the topography design, considering geometric characteristics of the project, restriction areas, deployment and operating costs. The proposed selection method was applied in a railway variant of eight kilometers, where 729 alternatives were analyzed and then set the best track for the study of horizontal alignment. The results were compared to the executive project and the same considerations used in the project were made which demonstrated the feasibility of the methodology.